Unraveling the Safety Profile of Nanoscale Particles and Materials From Biomedical to Environmental Applications - Gomes, Andreia C.; Sarria, Marisa P. (IntechOpen, 2018)
As nanomaterials become increasingly present in our daily lives, pertinent questions regarding their safety arise. Nanomaterial risk assessment, as in other areas, directs much of the effort worldwide in defining guidelines that may be translated into national or international directives. Nanomaterials encompass different entities, from nanoparticles to nanostructured materials, with specific effects over cells, tissues, organisms and ecosystems depending on their biophysical characteristics. Such interactions will directly affect the impact of novel nanotechnologies. This book aims to provide the reader with a comprehensive overview of the current state of the art in nanotoxicology, featuring the most important developments and critical issues regarding the use of and exposure to nanoparticles.